2021
DOI: 10.1007/s12671-021-01790-7
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of a Mindful Parenting Workshop for Parents of Adolescents and Young Adults Following Social Unrest in Hong Kong

Abstract: Objectives The social unrest that began in Hong Kong in 2019 became a threat to public mental health, such as for depression and post-traumatic stress disorders. A supportive family environment is the most effective protective factor for mental health problems for young people who are exposed to conflict and violence. This study investigated the outcomes of a brief mindful parenting workshop on parent mental health and family functioning. Methods Using a randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…While the present findings yield evidence for a possible role of positive parenting and family functioning in preventing adolescents' violent political participation, we cannot rule out the possibility that youths' participation in violent political actions created more family conflict and worsened parent-child relationships, especially when parents disapprove of their adolescent children's political participation or hold different political stances. In fact, several studies have reported increased intra-familial conflict and different levels of renegotiation in family relationships of active participants during the social unrest in Hong Kong (Ho et al, 2018;Lo et al, 2021). Lower relationship quality and lower congruence in family members' political attitudes predicted more serious subsequent family conflicts (Chan et al, 2018), which can lead to or worsen the existing mental health burden of adolescents and their family members.…”
Section: Discussionmentioning
confidence: 99%
“…While the present findings yield evidence for a possible role of positive parenting and family functioning in preventing adolescents' violent political participation, we cannot rule out the possibility that youths' participation in violent political actions created more family conflict and worsened parent-child relationships, especially when parents disapprove of their adolescent children's political participation or hold different political stances. In fact, several studies have reported increased intra-familial conflict and different levels of renegotiation in family relationships of active participants during the social unrest in Hong Kong (Ho et al, 2018;Lo et al, 2021). Lower relationship quality and lower congruence in family members' political attitudes predicted more serious subsequent family conflicts (Chan et al, 2018), which can lead to or worsen the existing mental health burden of adolescents and their family members.…”
Section: Discussionmentioning
confidence: 99%
“…Parent training that increases warmth and parental acceptance was recommended by Cheung et al (2018) based on their study of 217 Hong Kong families with 8-year-old children. Parent training based on mindfulness interventions did help Hong Kong parents of adolescents after the 2019 period of social unrest by improving family functioning and decreasing levels of depression (Lo et al, 2022). Yet, there have been no studies on parenting interventions for Hong Kong parents of young children after a social or health crisis such as COVID-19.…”
Section: Hong Kong Children’s Mental Health During Covid-19mentioning
confidence: 99%